علاقة أنماط التواصل الأسري لدى الأب بالصلابة النفسية عند الأبناء: دراسة وصفية لعينة من التلاميذ التعليم الثانوي - رحماني، شريفة; إزيدي، كريمة; حرطاني، أمينة (جامعة مصطفى اسطمبولي - كلية العلوم الإنسانية والاجتماعية, 2021)
يعد التواصل وسيلة مهمة للتفاعل وإشباع الحاجات النفسية خاصة في مراحل نمو الفرد، لذلك كان الهدف من هذه الدراسة هو البحث في علاقة الصلابة النفسية للأبناء بأساليب تواصل الأب. بعد التأكد من الخصائص السيكومترية لأداتي البحث (مقياس أنماط تواصل الأب ومقياس الصلابة النفسية)، تم تطبيقهما على عينة قوامها 305 تلميذ(ة) يدرسون بالقسم النهائي للتعليم الثانوي بمدينة وهران. أظهرت المعالجة الإحصائية للبيانات النتائج التالية: - أن مستوى الصلابة النفسية مرتفع عند الذكور والإناث إلا أنه مرتفع أكثر عند الإناث مقارنة بالذكور. - توجد فروق دالة إحصائيا من حيث الصلابة النفسية بين الأبناء الذكور المدركين لأسلوب تسامح الأب والأبناء غير المدركين لصالح المدركين ولأسلوب اللامبالاة لصالح غير المدركين - لا توجد فروق دالة إحصائيا من حيث الصلابة النفسية بين الأبناء الذكور المدركين لأسلوبي (حماية والعتاب) للأب والأبناء غير المدركين أما بالنسبة للإناث فلا توجد فروق بالنسبة لأساليب (حماية، عتاب، تسامح، لامبالاة) للأب
Communication is an important means of interaction and the satisfaction of psychological needs, especially in the individual's stages of development. Therefore, the aim of the study was to research the methods of father communication and its relationship to hardness on a sample of secondary education pupils (final section). After confirming the psychometric properties of the measures of parent communication patterns and psychological rigidity, the study was applied to 305 students in the final section of secondary education in the city of Oran, the statistical analysis of the research showed the following results: - The level of hardness is high in males and females, and the level of psychological hardness in females is high compared to that of males - There are statistically significant differences in terms of psychological rigidity between male children who are aware of the father’s tolerance method and the children who are not aware of the benefit of the conscious and the indifference in favor of the unaware. - There are no statistically significant differences in terms of psychological rigidity between male sons who are aware of my method (protection and reproach) for the father and unaware sons. As for females, there are no differences with respect to methods (protection, reproach, tolerance, indifference) for the father
Keywords: الصحة النفسية -- الصلابة النفسية -- أنماط التواصل الأسري -- الأباء -- طلبة المرحلة الثانوية